Palliative Care in Lung Cancer: A Review - Bade, Brett C.; Silvestri, Gerard A. (Seminars in Respiratory and Critical Care Medicine, 2016)
Lung cancer patients are at high risk of suffering due to severe and refractory symptoms, concomitant respiratory comorbidity, frequent disease progression, and treatment that can worsen and compromise quality of life. Palliative care (PC) has shown multiple benefits to cancer patients such as better quality of life, higher patient and family satisfaction, improved disease understanding, less symptom burden, fewer depressive symptoms, less aggressive end of life care, and even improved survival with early implementation. For these reasons, multiple societies have recognized PC as an essential component of lung cancer care, and early PC is recommended for patients with metastatic disease or refractory symptoms. Unfortunately, utilization of PC is both low and often near the end of life, increasing risk for suffering. Misconceptions about PC often underlie delayed referral to PC. This review summarizes the literature for utilization of PC in lung cancer and focuses on patient benefits, misconceptions, barriers, and implementation.
Keywords: lung cancer; palliative care; symptom control; end-of-life